Use of Pre-Injection Diffusion of Local Anaesthetic as a Means of Reducing Needle Penetration Discomfort - Kuscu, Ozgur Onder (Acta Stomatol Croat, 2014)
AIM: To determine if pre-injection diffusion of local anaesthetic solution influences the discomfort of needle penetration in the palate. METHODS: A placebo-controlled, randomised, double-blind split-mouth investigation was conducted. 25 healthy adult volunteers were recruited and each received two needle penetrations in a random order during one visit. The penetration sites were 1 cm from the gingival margin of the first maxillary premolars on each side of the mouth. 30 gauge-13 mm needles which were attached to syringes that contained either 2% lidocaine with 0.125mg/ml epinephrine or physiological saline were used. For each penetration an operator encouraged a drop of solution to appear at the end of the needle and placed this drop with the bevel of the needle flat on the palate for 20 seconds. The discomfort was noted on a 100 mm visual analogue scale with end points marked “No pain” and “Unbearable pain”. RESULTS: There was no significant difference in penetration discomfort between solutions, (mean VAS = 26.80±19.36mm for lidocaine and 26.20±18.39mm for saline) however the 2nd penetration was significantly more uncomfortable than the first (mean VAS = 31.00±19.84 mm and 22.00±16.65 mm respectively). CONCLUSION: Pre-injection diffusion of local anaesthetic solution did not influence the discomfort of needle penetration in the palate.